Development and validation of a yeast high-throughput screen for inhibitors of Aβ42 oligomerization - Sei-Kyoung Park; Scott D. Pegan; Andrew D. Mesecar; Lisa M. Jungbauer; Mary Jo LaDu; Susan W. Liebman (The Company of Biologists, 2011)
SUMMARY Recent reports point to small soluble oligomers, rather than insoluble fibrils, of amyloid β (Aβ), as the primary toxic species in Alzheimer's disease. Previously, we developed a low-throughput assay in yeast that is capable of detecting small Aβ42 oligomer formation. Specifically, Aβ42 fused to the functional release factor domain of yeast translational termination factor, Sup35p, formed sodium dodecyl sulfate (SDS)-stable low-n oligomers in living yeast, which impaired release factor activity. As a result, the assay for oligomer formation uses yeast growth to indicate restored release factor activity and presumably reduced oligomer formation. We now describe our translation of this assay into a high-throughput screen (HTS) for anti-oligomeric compounds. By doing so, we also identified two presumptive anti-oligomeric compounds from a sub-library of 12,800 drug-like small molecules. Subsequent biochemical analysis confirmed their anti-oligomeric activity, suggesting that this form of HTS is an efficient, sensitive and cost-effective approach to identify new inhibitors of Aβ42 oligomerization.